2235. A Collaborative Drug Therapy Management Model for the Treatment of Hepatitis C Virus (HCV) in an Urban Clinic. (26th November 2018) - Vibhakar, Sonia; Nowicki, Diana; Huhn, Greg; Goldberg, Rebecca; Adeyemi, Oluwatoyin
Abstract: Background: Direct-acting antivirals (DAAs) have changed the paradigm of HCV treatment due to high-sustained virologic response (SVR) rates and minimal adverse events. Prior authorizations, complex treatment criteria, and inadequate clinic staffing to meet demands of screening efforts may prevent access to treatment. Recent literature suggests that pharmacist involvement in HCV treatment can optimize care. We present a clinic protocol with collaborative drug therapy management to alleviate HCV treatment burdens. Methods: A retrospective review of patients referred and evaluated for HCV treatment between February 2014 and April 2018 at the Ruth M. Rothstein CORE Center. Exclusion was no SVR12 data. Demographic data along with HCV RNA at Week 4, end of treatment, and 12 weeks thereafter were collected. Results: Of 682 treatment referrals, 76 patients were denied or ineligible, two referred to study, and six not treated (lost to care, incarceration, or death). Of the 598 patients treated, complete data were available for 430. Of the remaining 168 patients, 72% have upcoming appts, 26% lost to follow-up, and 2% died. Mean age was 57.6 years (range 22–82), 70.5% male, 67% black, 17.2% Hispanic, 12.8% White; 203 were (47.2%) HCV/HIV co-infected. Majority were treatment naïve (86.3%) and cirrhotic (42.1%) with a median Fibro Scan of 13 (range 3.4–75). Most patients received ledipasvir/sofosbuvir (70%). Overall SVR rate was 93.5% (402/430); HIV co-infected patients 94.6% (192/203) and mono-infected patients 92.5% (210/227). Conclusion: A collaborative approach in HCV treatment allows us to overcome adherence barriers such as health literacy, medication acquisition issues, and drug interactions, as well as increase clinic productivity. A retrospective study may not capture all pharmacist interventions that prevent lapses in therapy such as frequent pharmacy calls and insurance resolution. However, this study shows that with an established clinic protocol and support of a multi-disciplinary team, high SVR rates are maintained, even in the large proportion of cirrhotic patients in our cohort. As clinic referrals continue to grow, additional staff may further support organizational work flow. Disclosures: G. Huhn, Gilead: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; ViiV Healthcare: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Janssen: Grant Investigator and Scientific Advisor, Consulting fee and Grant recipient; Theratechnologies: Scientific Advisor, Consulting fee; Proteus: Grant Investigator, Grant recipient.